Exploring Communication Strategies in EFL Conversations: A Study of Job"‘Seeker and Employee Students in an English Course - Haryani, Haryani; Febrianto, Aziza Restu; Rahmawati, Yusi; Sulistyorini, Dwi (Journal of English Education Program, 2025)
When learning English as a foreign language, students sometimes need help, such as a lack of competence and practice; they know the language but must learn how to use it correctly. For those reasons, students need a communication strategy to solve their problems. Therefore, this study aims to identify and analyze the communication strategies used by job seekers and employee students in an English Course Semarang during their conversation class. Employing a qualitative research method, data were collected through classroom observations, interviews, and transcription of audio recordings conducted over two weeks in February 2024. The study applied Tarone and Casper's theoretical framework to classify communication strategies. The findings reveal that topic avoidance and language switching were the most frequently used strategies (each 25.38%), followed by code-switching (20.78%), appeal to authority (19.24%), and message abandonment (9.23%). These findings underscore the importance of fostering an engaging classroom atmosphere that encourages learners to communicate actively and confidently in English. The practical implications of this research enable teachers to enhance speaking activities with guided reflection, allowing students to analyze and refine their strategies in real time.